The Organoleptic Test Formulations Snakehead Fish Flour Based Functional Cookies as An Alternative Snack For Stunting Toddlers - Helmizar Helmizar; Putri Aulia Arza; Restu Sakinah; Susmiati Susmiati (Universitas Andalas, 2021)
The substitution of Snakehead fish flour to make the cookies have the function of increasing nutrient. This study analyzes the effects of Snakehead fish flour on the sensory characteristics of cookies. This experimental study used a completely random design. The first step of the study was to characterize and develop snakehead fish flour. The second step was to determine functional cookie formulation with four treatments: 0%, 10%, 15%, and 20% snakehead fish flour. Cookies were then evaluated for their hedonic evaluation. As the results, the organoleptic study in the form of a hedonic test for 30 semi-trained panelists showed all categories except taste were not significantly different at p>0.05. The highest acceptance percentage for adding snakehead fish flour was 20% in taste significantly. In conclusion, the acceptability in the taste of respondents showed that snakehead fish flour treatment had a significant effect (p<0.05).